Effect of replacing corn meal with passion fruit peel in laying hen feed - Phonmun, T; Subanarat, T.; Paengkoum, P.; Liang, Juan Boo (2011)
The purpose of this study was to determine the effect of replacing corn meal with passion fruit peel on production performance in laying hens. Thirty experimental units (Sixty commercial breed laying hen) with initial body weight of 1.8 ± 0.01 kg were randomly assigned in randomized complete block design (RCBD). The experimental treatments were five different levels of passion fruit peel in the ration. The result showed that final body weight (BW) was significant different (P<0.05), with 10% passion fruit peel group exhibiting higher BW than the other groups, while the hens fed 20% passion fruit peel had the lowest BW, because of reduced feed intake. Egg weight in the 10% passion fruit peel in diet was also higher than the other groups (P<0.05) but not with 20% passion fruit peel group. The total egg production of 20% passion fruit peel in diet was lower than the control while the other treatment groups were not different with the control. Although cost of feed was not significant different (P>0.05) that decreasing when increase passion fruit peel in ration but the data show that cost of feed/egg 1 kg not decrease. Present data showed that passion fruit peel can replace corn meal up to 15% in diet which no effect on production performance of laying hens.